Crystal structure and cation off-centering in Bi(Mg 1/2Ti 1/2)O 3 - Malliga Suewattana (2018)
We investigate the structure of Bi(Mg 1/2 Ti 1/2 )O 3 using first-principles calculations. Electric field gradients are reported. The qualitative tilts of the perovskite octahedra are in accord with previously reported x-ray results, but we find significant differences in atomic positions. These amount to as much as 0.5, with the primary differences from the reported structure being the presence of substantial cation off-centerings both on the A site and on the B site in the calculated structure. Implications for this compound as the end point of a solid solution with a morphotropic phase boundary are discussed. © 2012 American Physical Society.